Environmental analysis of construction and demolition waste in urban areas using LCA tools: case study of Portugal (Aveiro) - Karanovic, Nikola (2022)
Construction and demolition (C&D) waste derives from activities such as the construction, renovation and demolition of infrastructures. The goal of this research is to improve understanding of the impacts of C&D waste management and to promote better C&D waste management planning. This thesis descrbies environmental analysis of C&D waste management in Aveiro (Portugal) and application of materials flow analysis (MFA) by analysing two scenarios (MFA scenario I, which describes current situation of C&D waste management system, and MFA scenario II, which follows the EU waste framework directive that encourage the reuse of construction materials and products. Analysing C&D waste fractions through the processes of recovery (R1- R13) and disposal, by applying impact methods ReCiPe (midpoint) and IPCC 2013 (Climate Change GWP100a), it is concluded that parameter “Waste C&D inert fraction” has the highest contribution in terms of impacts to the environment in all the analysed impact categories. Cadmium, chromium, copper, mercury, lead and zinc are substances of environmental concern and those elements are analysed throughout C&D system of Aveiro by applying substance flow analysis approach (MFA/SFA). During the processing of C&D waste, analysed heavy metals dissipate to the air, soil and water. In the analysed processes, zinc has highest constribution (in the context of dissipation) to the air, soil and water. Theoretical approach for the relationship of MFA/SFA and dissipation of analysed heavy metals is suggested. The obtained results can be used to define future strategies for C&D waste management, while the developed method can be applied for development and evaluation of new scenarios and different municipalities, with the aim of improving C&D waste management systems at all levels.